Sintesis Membran Poliuretan dari Asam Lemak Bebas Teroksidasi Tolulen Diisosianat - Marlina, Marlina (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Polyurethane (PU) membranes was prepared by reacting the free fatty acids and fatty acids that have been oxidazed from castor oil with a 2,4-toluen di-isocyanate (TDI). He effect of of monomer composition, temperature, and polymerization time was studied on the performances of flat sheet membrane. Experimental results showed that the optimum conditions of the membrane synthesis from free fatty acid by oxidation-methylation was obtained at ratio of 1.2: 0.56 (mol / mol), temperature of 100 C and polymerization time of 5 minutes. The resulting membranes are transparent, elastic, homogeneous, robust and has a glass transition point of 127.4 C and had stensile strength about 41.7 MPa. Infraredspectrum (IR) observation showed that the persistence of the peak CO from -NCO at wavenumber 2272.9 cm-1, whereas the -OH group was disaapear at wave numbers 3100-3300 cm-1. This indicated that the polymerization reaction of PU membrane synthesis from free fatty acids was done successfully.Keyword: Castor oil, free fatty acids, inframerah (IR), 2,4-tolulen di-isocyianat (TDI)